2007
DOI: 10.1007/s10096-007-0438-6
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired and hospital-acquired candiduria: comparison of prevalence and clinical characteristics

Abstract: Hospital-acquired candiduria (HAC) is a well-known finding, related to severely ill patients, prolonged antibiotic treatment, use of catheters, and invasive procedures. However, the risk factors and clinical significance of community-acquired candiduria (CAC) has not yet been described. In this study, the prevalence and clinical characteristics of CAC and HAC were compared. Demographic and clinical data from all patients with positive urinary cultures sent to the bacteriology laboratory of the Haemek Medical C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
4
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 24 publications
3
26
4
3
Order By: Relevance
“…Consistent with our observations, Colodner et al also reported higher incidence of CA-UTI in females than males. However, in this study patients were significantly younger compared to the HA-UTI group in there finding [18].…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…Consistent with our observations, Colodner et al also reported higher incidence of CA-UTI in females than males. However, in this study patients were significantly younger compared to the HA-UTI group in there finding [18].…”
Section: Discussioncontrasting
confidence: 45%
“…Recent studies highlight the changing epidemiology of community and nosocomial candiduria [6,7,14,18]. Our data showed that C. albicans remained as the prominent species isolated from urine cultures in both community and hospital setting, 85% and 68% respectively.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Even in adults, CFU criteria to diagnose candiduria range from 10 3 to 10 5 CFU/ml urine. In some studies candiduria is even differentially defined for women and men (57). Treatment trials funded by the National Institutes of Health generally use the lower CFU cutoff (10 3 ) as their definition (241).…”
Section: Definition and Diagnosis Of Candiduriamentioning
confidence: 99%